Gerontariado: The old age of the XXI century and the transformations in the world of work - da Rocha , Marlene Pereira; Ribeiro , Bruno Chapadeiro (Seven Editora, 2023)
The new historical phenomenon emerging in the twenty-first century, marked by population aging, should increase the physical and mental illness of the aging working class – the gerontariate – composed of a group of people over 45 years of age, highly educated. This age group should start to occupy the labor market in the coming decades, at the risk of unequal and undignified conditions. Thus, the "problem of gerontariado" is projected: the reflection on the working conditions, productivity, and health of older and elderly workers. In this context, this theoretical essay aims to reflect on the precariousness of the work of older and older people in the twenty-first century. The group of gerontariate that represents the most complex workforce, with skills, talents, and high competencies is located before a set of risks of precariousness, a part resulting from the vulnerabilities linked to the fragility in the training of workers and, still, due to the precariousness of the wage conditions of exploitation of the labor force. This reduces the opportunities of "older" workers in the evolution of their professional careers. The increase in the average age of people in this context portrays, in part, the fact that older workers reproduce a growing group of people employed or looking for work. On the other hand, older workers are less likely to be unemployed, but if so, they take longer, on average, to return to work, being more susceptible, therefore, to the employment crisis, that is, if they become unemployed, they will have more difficulty inserting themselves into the field of work. To this end, employers are suggested greater efforts to maintain and update the skills of these workers, avoiding the obsoleteness of the workforce is the responsibility of the worker himself or the lack of public policies capable of accounting for the qualification of this group. DOI:https://doi.org/10.56238/alookdevelopv1-114